Diversity and ecological importance of ferns in Nigerian Institute for oil palm research (nifor) oil palm (elaeis guineensis jacq.) plantation in edo state, Nigeria (2018)
Epiphytic plants and ferns are important components of oil palm ecology in rain forest rainforest ecosystem. The study was conducted at the Nigerian Institute for Oil Palm Research (NIFOR) in Benin City, Nigeria 06033`N, 05 037`E, 149 m above sea level during the wet season of 2015. Herbaceous floristic sampling of the plantation followed systematic sampling technique using 180 square 0.5 m2 quadrats that were laid along two line transects laid 250 m apart over a total of nine plots of 40 hectares each. Data collected on species composition, abundance, frequency, density, and soil physicochemical properties following standard procedures. Data were analysed for relative importance value (RIV), species diversity, multivariate relations (numerical ordination and classification), and allometric assessment for carbon sequestration. Thirty nine (39) species of herbaceous flora in twenty two (22) families were enumerated in the site. The RIVs of four herbaceous flora were highest with invasive species Nephrolepis undulata (a fern) and Chromolaena odorata having the highest RIVs of 13.04 and 11.72 respectively. It was lowest (0.13) for Perotis indica in the family Rubiaceae Rubiaceae. The Shannon-Wiener index (3.16), indicated a high diversity and co-interaction among the herbaceous flora; evenness index was near medium (0.60) indicating a moderately even distribution of species in the plots. Stand ordination amalyses indicated similarities of herbaceous components and possible stable succession in many plots, while classification and cluster analyses revealed Nephrolepis undulata as a strict negative preferential, possibly due to its epiphytic nature; and Chromolaena odorata as leading non-preferential, possible due to its ubiquity. Carbon stock for the plantation soil was estimated at 69.54 tons carbon/hectare with a carbon sequestration efficiency of 87.96%. Soil of the plantation was mainly loamy and slightly acidic (pH range = 5.13 - 6.10). These findings show ferns are important component of NIFOR plantation with potentials to serve as a bio-indicator of ecosystem change. The herbaceous flora of NIFOR plantation was diverse and essential contributors to its soil high carbon stock and sequestration efficiency. Further studies should be done to assess the correlates of floristic variation with other microhabitat factors in oil palm plantations at NIFOR and in other agro-ecological zone.